2018
DOI: 10.1002/jms.4300
|View full text |Cite
|
Sign up to set email alerts
|

Analyte‐substrate interactions at functionalized tip electrospray ionization mass spectrometry: Molecular mechanisms and applications

Abstract: Conventional electrospray ionization mass spectrometry (ESI‐MS) commonly uses capillary tip for sample introduction and ionization. In recent years, ESI‐MS using noncapillary substrate tips has attracted growing interest as it allows separation and enrichment of analytes from complex samples due to analytes‐substrate interactions. In this work, model mixtures and functionalized tips were employed to investigate the molecular mechanism of the analyte‐substrate interactions. The mixtures were directly loaded on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The signal of Neo ( m/z 254) in raw urine (0.1 μg/mL) was used for investing the responses of different substrate tips, as shown in Figure A. It can be seen that the hydrophilic Neo was obtained the best signal on the hydrophobic tip, ie, PE tip, because of the weak analyte‐substrate interactions on the tip‐ESI . Loading solvent could also be employed as the extraction and spray‐ionization solvent for tip‐ESI‐MS analysis of real samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The signal of Neo ( m/z 254) in raw urine (0.1 μg/mL) was used for investing the responses of different substrate tips, as shown in Figure A. It can be seen that the hydrophilic Neo was obtained the best signal on the hydrophobic tip, ie, PE tip, because of the weak analyte‐substrate interactions on the tip‐ESI . Loading solvent could also be employed as the extraction and spray‐ionization solvent for tip‐ESI‐MS analysis of real samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, both Bio and Neo are highly hydrophilic analytes; it is found that the interaction between analytes and hydrophilic tips (eg, wooden tip) could reduce the detection sensitivity . It is reported that high‐hydrophobic tips such as polyethylene (PE) allowed the better adsorption of hydrophobic compounds compared with low‐hydrophobic tip such as wooden tips, due to the analyte‐substrate interaction . Therefore, there is an expectation to seek hydrophobic materials for enhanced detection hydrophilic analytes from complex samples .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years, the development of ambient desorption/ionization MS have greatly facilitated direct analysis of food samples with little or no sample pretreatment, and most of the ambient desorption/ionization techniques employ charged spray, gas jet, laser, or plasma beam to desorb and ionize analytes from complex matrices . More recently, various tip‐electrospray ionization (tip‐ESI) methods that employed tip‐based materials as ESI emitters included but not limited to paper tip, wooden tip, graphite sheet, swab tip, ballpoint tips, metal needle, metal foil, chip‐tip, and biological tissue have also been successfully developed for direct sample analysis, and the related mechanisms and applications have also been investigated in our previous work . In this kind of tip ESI methods, the food samples could be loaded on the tip, and then the solvent and high voltage are applied onto the tip for generating an electrospray.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 More recently, various tip-electrospray ionization (tip-ESI) methods that employed tip-based materials as ESI emitters included but not limited to paper tip, wooden tip, graphite sheet, swab tip, ballpoint tips, metal needle, metal foil, chip-tip, and biological tissue have also been successfully developed for direct sample analysis, [10][11][12][13][14][15][16][17][18][19][20][21][22] and the related mechanisms and applications have also been investigated in our previous work. [22][23][24][25] In this kind of tip ESI methods, the food samples could be loaded on the tip, and then the solvent and high voltage are applied onto the tip for generating an electrospray. Particularly, various raw food materials including eggs, meats, bones, and vegetables, fruits, and herbs have been successfully analyzed by the tip ESI methods.…”
Section: Introductionmentioning
confidence: 99%